Application of foot massage therapy to reduce pain scale of elderly with rheumatoid arthritis - Nadi Aprilyadi; Rachmad Aprilio; Wulan Martalina; Zuraidah Zuraidah; Wahyu Dwi Ari Wibowo (PAGEPress Publications, 2024)
Rheumatoid Arthritis (RA) is a chronic autoimmune disorder characterized by systemic inflammation, joint damage, and persistent pain, particularly in older adults. The debilitating nature of RA significantly impairs individuals' quality of life, leading to diminished independence and increased reliance on pharmacological interventions. While pharmaceutical treatments play a crucial role in managing RA symptoms, complementary and alternative therapies, such as massage, have garnered attention for their potential to alleviate pain and improve overall well-being. This study adopts a descriptive approach to examine the efficacy of foot massage as an intervention for RA-related pain in older adults. Two participants diagnosed with RA were selected for the case study. Family nursing care principles were integrated into the intervention to provide holistic support. Pain scale assessments were conducted before and after each foot massage session to measure changes in pain intensity. Analysis of the data revealed a significant reduction in pain intensity among participants following the foot massage sessions. Pain levels decreased from moderate to mild, indicating the efficacy of  foot massage in alleviating RA-associated pain in older adults.The findings of this study support the notion that foot massage can serve as a viable intervention for managing RA-related pain in older adults. The mechanisms underlying the efficacy of foot massage, including its ability to stimulate vasodilation and enhance endorphin production, highlight its potential therapeutic benefits for individuals grappling with RA. Foot massage emerges as a promising adjunctive therapy for alleviating pain and improving the well-being of older adults living with Rheumatoid Arthritis. Integrating foot massage into holistic care approaches can enhance pain management strategies and contribute to the overall quality of life for individuals affected by this debilitating condition. Further research is warranted to explore the long-term effects and optimal frequency of foot massage in RA management.